Sleep duration and progression to sarcopenia in Japanese community‐dwelling older adults: a 4 year longitudinal study. Issue 4 (30th June 2021) - Nakakubo, Sho; Doi, Takehiko; Tsutsumimoto, Kota; Kurita, Satoshi; Ishii, Hideaki; Shimada, Hiroyuki
Abstract: Background: Identifying factors that contribute to the development of sarcopenia in older adults is a public health priority. Although several studies have examined the association between sleep duration and sarcopenia, additional evidence is needed to reveal the causality of this association, especially from a longitudinal study. The purpose of the present study was to examine whether sleep duration was associated with the progression to sarcopenia and its subcomponents among community‐dwelling older adults in Japan. Methods: A total of 3918 older community‐dwelling people (mean age: 73.2 ± 6.0 years, 51.8% female) included in the National Center for Geriatrics and Gerontology Study of Geriatric Syndromes were analysed. Sleep duration was assessed using a self‐reported questionnaire. Logistic regression analysis was used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) of progression of sarcopenia at Wave 2 (4 years later), according to the three categories of sleep duration [short: ≤6.0 h, medium: 6.1–8.9 h (control), & long: ≥9.0 h)] at Wave 1. Results: The numbers in each group in the second wave among the total sample were as follows: short 403 (10.3%), medium 2877 (73.4%), and long 638 (16.3%). Significant associations with the progression of sarcopenia were found in the long sleep duration group compared with the medium one, even after adjustment for other covariates (OR 1.66, 95% CI: 1.02–2.69, P = 0.040). Long sleep duration was significantly associated with slow gait (OR: 1.55, 95% CI: 1.17–2.06, P = 0.002) and low grip strength (OR: 1.34, 95% CI: 1.00–1.78, P = 0.047) but was not associated with low muscle mass (OR: 1.33, 95% CI: 0.74–2.38, P = 0.343). Conclusions: This study revealed that long sleep duration was associated with an increased risk of progression to sarcopenia among older adults.